2016
DOI: 10.3109/08820139.2016.1153649
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory Effect of Nigella sativa Oil on T Lymphocytes in Patients with Rheumatoid Arthritis

Abstract: This study gives strength to the potential relevance of NS in clinical management of RA through modulation of T lymphocytes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(52 citation statements)
references
References 43 publications
3
45
1
3
Order By: Relevance
“…A clinical study recruited 24 patients with allergic rhinitis sensitive to house dust mites and 7 healthy volunteers, administered with conventional doses of allergen-specific immunotherapy for 30 days. After a month of immunotherapy, 12 patients among 24 received the 2 g/day oral supplementation of N. sativa seed for 30 days that resulted in significant raise of CD8 counts and polymorphonuclear leukocyte (PMN) along with improved clinical symptoms [ 47 ] and a randomized, double-blinded placebo-controlled clinical trial of 43 female patients with mild to moderate rheumatoid arthritis (RA) revealed that administration of capsules of 500mg N. sativa oil 2 times daily for 2 months resulted in modulation of T lymphocytes such as decreased CD8+ (suppressive lymphocyte), and increased percentage of CD4+CD25+ and the ratio of CD4+/CD8+ [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…A clinical study recruited 24 patients with allergic rhinitis sensitive to house dust mites and 7 healthy volunteers, administered with conventional doses of allergen-specific immunotherapy for 30 days. After a month of immunotherapy, 12 patients among 24 received the 2 g/day oral supplementation of N. sativa seed for 30 days that resulted in significant raise of CD8 counts and polymorphonuclear leukocyte (PMN) along with improved clinical symptoms [ 47 ] and a randomized, double-blinded placebo-controlled clinical trial of 43 female patients with mild to moderate rheumatoid arthritis (RA) revealed that administration of capsules of 500mg N. sativa oil 2 times daily for 2 months resulted in modulation of T lymphocytes such as decreased CD8+ (suppressive lymphocyte), and increased percentage of CD4+CD25+ and the ratio of CD4+/CD8+ [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Anecdotic reports suggest that immunological benefits can be gained in patients with autoimmune diseases including SLE and rheumatoid arthritis from simple measures, including oral honey drink and Nigella sativa oil 152 or powder as nutritional support measures. It is reported that wet cupping therapy (Al-Hijamah) can clear patients’ blood from autoantibodies, inflammatory mediators and immunological noxious substances.…”
Section: Third-line Treatmentsmentioning
confidence: 99%
“…However, 2 studies in animal models [56,69] did not report any significant effect of N. sativa in RA. In addition, human studies [52][53][54][55][56] have suggested favorable effects of N. sativa on clinical and immunologic parameters of RA; however, no change or improvement of inflammatory and oxidative biomarkers was declared in the clinical trials [53,55]. The controversy in findings between clinical and experimental investigations may be attributed to the differences in the measures of inflammatory, oxidative, and anti-oxidative markers in vivo or in vitro, as well as intensity and the type of stimulators of inflammation and oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effects of N. sativa on RA prevention and treatment have been investigated in recent y, and some hopeful findings have been obtained from experimental investigations [46][47][48][49][50][51] and clinical trials [52][53][54][55][56]. It has been suggested that N. sativa can influence the main traits of RA via various procedures [57].…”
Section: A Systematic Review Of the Potential Effects Of Nigella Satimentioning
confidence: 99%